2017
DOI: 10.3390/v9040076
|View full text |Cite
|
Sign up to set email alerts
|

Single-Round Infectious Particle Antiviral Screening Assays for the Japanese Encephalitis Virus

Abstract: Japanese Encephalitis virus (JEV) is a mosquito-borne flavivirus with a positive-sense single-stranded RNA genome that contains a big open reading frame (ORF) flanked by 5′- and 3′- untranslated regions (UTRs). Nearly 30,000 JE cases with 10,000 deaths are still annually reported in East Asia. Although the JEV genotype III vaccine has been licensed, it elicits a lower protection against other genotypes. Moreover, no effective treatment for a JE case is developed. This study constructed a pBR322-based and cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 49 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…TE671-CprME stable cell line generated in our laboratory is a packing cell line expressing JEV structure proteins (C, prM, and E) which was described in our previous work [34]. TE671-CprME cells were culture in MEM, 5% FBS, and 500 µg/mL G418 (Sigma, Saint Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…TE671-CprME stable cell line generated in our laboratory is a packing cell line expressing JEV structure proteins (C, prM, and E) which was described in our previous work [34]. TE671-CprME cells were culture in MEM, 5% FBS, and 500 µg/mL G418 (Sigma, Saint Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…7 ). Moreover, a CMV promoter-launched JEV-EGFP replicon reported in our prior study 10 was used to ascertain whether CW-33A influences on the viral protein expression and genome synthesis (Figs 8 and 9 ). Fluorescent microscopy revealed that CW-33A reduced the green fluorescence in the replicon-transfected cells and inhibited replicon-induced CPE in TE-671 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After 15-min incubation, 10,000 cells from each sample are directly evaluated using flow cytometry with a 488 nm/620 nm. In the infectivity inhibition assay with immunofluorescence staining, JEV-infected cells with an MOI of 0.05 were fixed, permeabilized, and blocked after a 24-h incubation with the indicated concentrations of CW-33 and CW-33A, as described in our report 10 . Cells were stained with rabbit anti-JEV-NS3 (GeneTex, Inc) and secondary AF546 conjugated antibodies (ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested optimal dilutions were 1:100-1:2000 for ICC/IFA, and 1:500-1:3000 for WB. This antibody has been utilized to study JEV [20], but not other members of the genus Flavivirus such as West Nile virus (WNV), dengue (DENV), and Zika virus (ZIKV). For the detection of NS4B protein in the present study, the anti-JEV NS4B antibody was diluted 1:150 (5.1 µg/mL) or 1:1500 (0.5 µg/mL) for IFA and WB assays, respectively.…”
Section: Antibodiesmentioning
confidence: 99%